Amino acid-modified ultrafine superparamagnetic iron oxide nanoparticles: fabrication, size characterisation and potential cytotoxicity and cell interaction - ALALI, Muqdam (2018)
The potential applications of transition metals-based nanoparticles are expanding in the biomedical field. Oxides of iron are the matter of investigation in this study where various preparations of ultrafine superparamagnetic iron oxide nanoparticles (USPIONs) were fabricated using flow injection technology with spinning disc reactor. Basically, two types of preparation parameters were examined; first, instrument-related (physical) parameters and, second, chemistry-related parameters. USPIONs fabricated by this instrument showed fine-tuning size adjustment. Subsequent surface modification of these nanoparticles produced hydrophobic, hydrophilic and neutral amino acids modified surface, whereby aminoacid ‘monomers’, rather than polymeric materials were used. Transmission electron microscopy (TEM), dynamic light scattering (DLS), zeta potential measurements, thermogravimetric analysis (TGA) and fourier-transform infrared-attenuated total reflection spectroscopy (FTIR-ATR) were employed to characterise the coated nanoparticles. The data show that ultrafine, 4-9 nm sized coated nanoparticles show good dispersion upon TEM imaging. Measurement of number of monomers molecules effectively associated with USPIONs suggest formation of multilayer of amino acid adsorbed on nanoparticles (NPs). Prediction of NPs- amino acid association mechanism by FTIR-ATR study reveals presence of either monodentate or bidentate molecular adsorption on the surface of USPIONs. In the second stage of the project, interactions of differently modified USPIONs with epithelial cell layer (model of intestinal epithelium) are now investigated. An intestinal adenocarcinoma cell line (Caco-2) is used for performing the in vitro studies. The toxicity of three types of USPIONs (Asp-, His-, and Phe-USPIONs) reveals that these particles have potential toxic effect on biological system. Relatively long term exposure to these particles (24 hours) with high concentration 250 µg/ml and more was found to enhance apoptotic mode of cell death. Cell-NPs interaction study displayed presence of different forms of cellular interaction which are supposed to be related to USPIONs surface chemistry. While some of Phe-USPIONs are found internalised and accumulated inside some cells, Asp-USPIONs exhibit different interaction mode where the cell membrane of most cells is covered with thin layer of NPs without significant cell penetration. This gives an indication that metal oxide NPs (USPIONs) that are associated by their surface with small molecules could render these NPs with aggravated toxicity and cell-NPs interaction and hence long term effect.